Influence of dietary nitrate supplementation on intermittent exercise performance - Wylie, L. J.; Bailey, S. J.; Kelly, J.; Blackwell, J. R.; Vanhatalo, A.; Jones, A. M (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Dietary nitrate (NO3-) supplementation has been shown to improve exercise tolerance during continuous high-intensity exercise in recreationally-active subjects (e.g., Bailey et al., 2009). However, the influence of NO3- on intermittent exercise performance is controversial. The purpose of this study was to assess the effect of NO3- on performance in a variety of intermittent exercise protocols commonly used in training and/or competition. Methods: Ten male recreational team-sport players were assigned in a double-blind, randomised, crossover design, to consume NO3--rich beetroot juice (BR; ~ 10.08 mmol NO3-/d) and NO3-- depleted placebo juice (PL; ~ 0.10 mmol NO3-/d) for 5 days. Subjects completed 24 x 6-s all-out sprints interspersed by 24 s of recovery, 7x 30-s all-out sprints interspersed by 240-s of recovery and 6 x 60-s self-paced maximal efforts interspersed by 60-s of recovery on days 3, 4 and 5 of supplementation, respectively. All sprints were completed on an electronically braked cycle ergometer for assessment of power output and work done. Pulmonary gas exchange was assessed in all tests. Results: On days 3-5 of supplementation, plasma [nitrite] was 237 % greater in BR compared to PL (P<0.01). In the 24 x 6-s sprint protocol, mean power was greater in sprints 1-6 (5 %; P<0.05), and tended to be greater in sprints 13-18 (3 %; P=0.08) and 19-24 (3 %; P=0.07) with BR. Across all 24 x 6-s sprints, mean power was 3 % greater (BR: 595 ± 87 vs. PL: 578 ± 79 W; P<0.01) and the respiratory exchange ratio was 4% greater (BR: 1.14 ± 0.04 vs. PL: 1.10 ± 0.02; P<0.05) with BR. Power indices, total work done and pulmonary gas exchange were not impacted by BR in the 7 x 30-s and 6 x 60-s tests (all P>0.05). Discussion: This study suggests that the extent to which NO3- might be ergogenic during intermittent exercise is dependent upon the interval duration, intensity and work:rest ratio. NO3- supplementation enhanced performance across a series of 6-s all-out sprints with a work:rest ratio of 1:4, but did not improve performance during repeated 30-s all-out sprints or 60-s self-paced maximal efforts with work:rest ratios of 1:8 and 1:1, respectively. These results suggest that NO3- supplementation has the potential to enhance performance in team sports.